Fabrizio Agnello. (2023). La memoria fotografica dell’architettura. Restituzioni prospettiche e ricostruzioni. Milano: FrancoAngeli. (diségno, 2023)
At first glance it looks like a book –another one!– on perspective restitution. But the contents –finally– are very different. Before focusing on the merits of this new contribution, it is important to point out that the main topic, presented in the subtitle (perspective restitution and ensuing reconstructions) could in fact appear to have already been extensively exploited as well as prevalently didactic in nature. But anyone who leafs through this publication will immediately grasp the intense creativity of a truly innovative approach to an issue rooted in history, but tackled in an absolutely contemporary manner. [read more]